Objective monitoring of cattle - Theurer, Miles E. (Kansas State University, 2015)
There are multiple modalities available to evaluate health or stress status of animals. The objective of my research was to evaluate different modalities including behavior, rectal and nasal temperature, and blood samples to determine the relationship with these outcomes of interest in bovine respiratory disease (BRD) events, environmental conditions, transportation, and Mannheimia haemolytica challenge model. The objective for the final project was to determine whether diagnostic sensitivity or specificity resulted in greater economic value for the industry using simulation models for identification of BRD. There was a positive association with rectal temperature and probability of not finishing the production cycle normally, but this relationship was not linear. Rectal temperature of feedlot calves at first treatment for BRD had limited value as a prognostic indicator of whether those calves would finish the production cycle normally. A positive association between rectal temperature and ambient temperature and temperature-humidity index was determined. Environmental conditions must be considered when rectal temperature is used as a diagnostic tool. At 48 hours after initiation of transportation there were no differences in body weight, rectal temperature, and time spent at various locations in the pen detected between transported and non-transported control heifers. Transportation of heifers during periods of high ambient temperatures caused transient changes in physiologic and behavioral indices of heifers. Calves challenged with Mannheimia haemolytica had more changes in behavior, body weight, and blood biomarkers during high ambient temperatures compared to control calves. Results of this study may guide research in development of objective assessment tools for identification and management of cattle affected with BRD during extreme summer conditions. For both low and high apparent prevalence cohorts, increasing diagnostic specificity resulted in more rapid, positive change in net returns compared to change in increasing sensitivity. Improvement of diagnostic specificity, perhaps through a confirmatory test or pen-level diagnostics, can increase diagnostic value. Mortality risk was the primary driver for net returns. Results from this study are important for determining future research priorities to analyze diagnostic techniques for BRD and provide a novel way for modeling diagnostic tests.
Keywords: Bovine respiratory disease complex; Diagnostic tools; Animal behavior; Physiology; Heat stress; Economic modeling